Plasma proenkephalin and neutrophil gelatinase-associated lipocalin predict mortality in ICU patients with acute kidney injury - Mengqin Zhang; Yang Yang; Luqi Zhu; Ke Cui; Sheng Zhang; Yinghe Xu; Yongpo Jiang (BMC Nephrology, 2024)
Abstract Background Acute kidney injury (AKI) is a common complication in patients admitted to intensive care unit (ICU) and mortality rates for this condition are high. To reduce the high incidence of short-term mortality, reliable prognostic indicators are required to facilitate early diagnosis and treatment of AKI. We assessed the ability of plasma proenkephalin (p‑PENK) and plasma neutrophil gelatinase-associated lipocalin (p‑NGAL) to predict 28-day mortality in AKI patients in intensive care. Methods This prospective study, carried out between January 2019 and December 2019, comprised 150 patients (100 male) diagnosed with AKI after excluding 20 patients discharged within 24 h and those with missing hospitalization data. Blood samples were collected to determine admission p-PENK and p-NGAL levels. The study outcome was 28‑day mortality. Results The mean patient age was 68 years (female, 33%). The average P‑PENK and p‑NGAL levels were 0.24 ng/µL and 223.70 ng/mL, respectively. P‑PENK levels >0.36 ng/µL and p‑NGAL levels >230.30 ng/mL were used as critical values to reliably indicate 28‑day mortality for patients with AKI (adjusted hazard ratios 0.785 [95% confidence interval 0.706–0.865, P<0.001] and 0.700 [95% confidence interval 0.611–0.789, P<0.001], respectively). This association was significant for mortality in patients in intensive care with AKI. Baseline p-PENK (0.36 ng/µL) and p-NGAL (230.30 ng/mL) levels and their respective cut-off values showed clinical value in predicting 28-day mortality. Conclusion Serum PENK and NGAL levels, when used in conjunction, improved the accuracy of predicting 28-day mortality in patients with AKI while retaining sensitivity and specificity.